2014
DOI: 10.3189/2014jog13j197
|View full text |Cite
|
Sign up to set email alerts
|

Interannual persistence of the seasonal snow cover in a glacierized catchment

Abstract: Knowledge of the spatial snow distribution and its interannual persistence is of interest for a broad spectrum of issues in cryospheric sciences. In this study, snow depths derived from airborne laser scanning are analyzed for interannual persistence of the seasonal snow cover in a partly glacierized mountain area (~36 km2). At the end of five accumulation periods, the snow-covered area varied by 16% of its temporal mean. Mean snow depth of the total area ranged by a factor of two (1.31–2.58 m), with a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 65 publications
15
51
0
Order By: Relevance
“…They suggest that "a reduction in precipitation from upslope lifting, and/or the exhaustion of precipitable water from ascending air masses" (Kirchner et al, 2014) might be the reason for the shape of the snow depthelevation relationship. Based on multi temporal point measurements, similar shapes had already been identified by Turcan (1975) and Holko (2000) for a 35 km 2 basin in the Low Tatra mountains (Slovakia). Both studies report on positive elevation gradients of snow below the tree line and a distinct decrease of snow storage in the summit region.…”
Section: T Grünewald Et Al: Elevation Dependency Of Snowsupporting
confidence: 67%
See 1 more Smart Citation
“…They suggest that "a reduction in precipitation from upslope lifting, and/or the exhaustion of precipitable water from ascending air masses" (Kirchner et al, 2014) might be the reason for the shape of the snow depthelevation relationship. Based on multi temporal point measurements, similar shapes had already been identified by Turcan (1975) and Holko (2000) for a 35 km 2 basin in the Low Tatra mountains (Slovakia). Both studies report on positive elevation gradients of snow below the tree line and a distinct decrease of snow storage in the summit region.…”
Section: T Grünewald Et Al: Elevation Dependency Of Snowsupporting
confidence: 67%
“…It is also important to note that this study is restricted to a handful of selected study sites and single dates in one single year. The transferability of the results to other years remains limited, even though several studies have identified a high temporal consistency of snow depth between different seasons (Deems et al, 2008;Schirmer et al, 2011;Helfricht et al, 2014). However, it may not be assumed that such a consistency is valid for all mountain sites.…”
Section: Discussionmentioning
confidence: 90%
“…Along the profiles, however, the spatial resolution was higher and an interpolation scheme should be able to utilize this information to fill the gaps between profiles. Because snow accumulation reveals trends in the mean accumulation, e.g., with elevation, and differences in the variability, such as through higher wind speeds at higher elevations (Helfricht et al, 2014), it must be considered a non-stationary process. To take this into account we applied geographically weighted regression (GWR) that allowed for spatial variations in the influence of the explaining variables (Brunsdon et al, 1996;Fotheringham et al, 1998).…”
Section: Generalizing Snow Accumulation Distributionmentioning
confidence: 99%
“…; Helfricht et al . ). However, lateral redistribution of snow from mountain slopes and wind transport of snow to glacier surfaces increases snow cover variability on glaciers (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…; Helfricht et al . ). If lidar data are used, a considerable underestimate of actual snow depths in the accumulation area and an overestimate of actual snow depths in the ablation area by using lidar data can be expected at large alpine glaciers with a high mass turnover.…”
Section: Introductionmentioning
confidence: 97%